Estudos computacionais de potenciais inibidores da enzima N-Miristoiltransferase de Plasmodium falciparum e Leishmania donovani - Garcia, Letícia Santos (2017)
Malaria and leishmaniasis are neglected diseases that afflect thousands of people worldwide. Malaria is a disease caused by protozoa of the genus Plasmodium. In recent years the resistance of the parasite to several drugs, including the drug of first choice for the treatment of the disease, has been verified. Leishmaniasis is caused by protozoan parasites of the genus Leishmania and chemotherapy for this disease is also unsatisfactory, presenting several side effects, high toxicity and high cost. N-myristoylation of proteins is catalyzed by N-myristoyltransferase (NMT), an essential target for Plasmodium falciparum and Leishmania donovani. In order to study new NMT inhibitors, quantitative analysis of the structure-activity relationship in the fourth dimension was used. In the work of malaria, 83 compounds were used and ten alignments were performed. This work suggested a good correlation with the experimental results, besides allowing the planning of new inhibitors of Plasmodium falciparum NMT. Already the work of leishmaniasis was applied to a series of 77 NMT inhibitors of Leishmania donovani. Then, three new compounds were proposed using the generated models. In addition, molecular docking was performed to investigate the binding affinities and interaction modes between the proposed compounds and the NMT active site. Furthermore, an ADME (absorption, distribution, metabolism and excretion) evaluation was performed and potential inhibitors demonstrated satisfactory pharmacokinetic properties.